The Legal Barriers to Foreign Direct Investment in South Sudan's Oil and Gas Sector/ Industries - Basimanyane, Dorcas K. (University of Pretoria, 2025)
Mini Dissetation (LLM (International Trade and Investment in Africa))--University of Pretoria, 2025.